PENGARUH PEMBERIAN INFUSA DAUN LABU SIAM (Sechium edule) TERHADAP KADAR HEMOGLOBIN DAN NILAI HEMATOKRIT TIKUS PUTIH (Rattus norvegicus) ANEMIA (The Effect of Chayote (Sechium edule) Leaves Infusion on Haemoglobin and Hematocrit Level of Anemic White Rat (Rattus norvegicus)) - Zuhrawati Zuhrawati; Nuzul Asmilia; Asri Rizky; Zuraidawati Zuraidawati; Nazaruddin Nazaruddin; Mulyadi Adam; Muttaqien Muttaqien (Universitas Syiah Kuala, 2015)
The aim of this research was to evaluate the effect of chayote (Sechium edule) leaves infusion on hemoglobin and hematocrit level of anemic rat (Rattus norvegicus). Twelve anemic hemorrhagic male rats strain Wistar with body weight ranging from 175-200 g were used as sample in this research. Rats were divided randomly into 3 treatment groups, each group consist of 4 rats. The control group (P0) was not given chayote leaves infusion. Group P1 and P2 were given chayote leaves infusion with the concentration of 25% and 50% respectively, with dose of 1 ml per 200 gram body weight. Rats were fed with standard commercial food (Turbo feed) and aquadest ad libitum. The rats were treated anemic by taking 20% blood from total blood volume prior to administration of chayote laeves infusion. Chayote leaves infusion was given for 10 days consecutively. Blood sampling was carried out on day 0, 5, and 10 via caudal vein. Data were analyzed using anlysis of variance (ANOVA) Split-Plot pattern. The result showed that chayote leaves infusion increase level of hemoglobin and hematocrit in experimental rats. In conclusion 25% concentration of chayote leaves infusion is more effective than 50% concentration.Key words: anemia, chayote leaves, hemoglobin, hematocrit